READING MATERIAL DEVELOPMENT OF DESCRIPTIVE TEXT BASED ON PROBLEM BASED LEARNING GRADE X STUDENTS OF ELECTRICAL ENGINEERING AT SMK SINAR HUSNI MEDAN - Nisfu Sari; Busmin Gurning; Juli Rachmadani Hasibuan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
The aims of this research were: (1) to find out the suitable the reading materials for grade eight students of SMP N 1 Kotapinang, (2) to find out how to design English reading materials based on problem based learning which is suitable to the needs of students of SMK Sinar Husni Medan. The research was conducted by Research and Development (R & D) design through six stages; gathering information and data,analyzing data, designing materials, validating by experts, revising, and final product. The subject of this research was class X students of SMK Sinar Husni Medan consisting of 38 students. The instrumentations for collecting the data were questionnaire and interview. After , anlyzing the data, the researcher got the students’ needs. The data were gathered by administering interview and distributing the questionnaire to 38 students to get the students’needs. The interview and questionnaire results proved that the students needs English reading materials which cointain English relating to their daily life environment. Thus, developing English reading mateials were descriptive text. The products have been validated by experts. The average scores are 5,17 from English Lecturer and 4,68 from English Teacher. It means the developing materials categorized as relevant or appropriate for Grade X Students of SMK Sinar Husni Medan. This research developed Problem Based Learning materials. It covers reading skill and consists of introduction, main lesson and reinforcement tasks. The input was in the form of written texts, vocabulary list and grammar explanation. The students were encouraged to do discussion and involve in active investigation to solve and do tasks. Most of the tasks are done in a small group discussion and in pairs. Based on the results of materials evaluation, the content, language, presentation and graphic of the developed materials are considered appropriate. Keywords : Research and Development (R & D, Problem Based Learning ,Descriptive Text